The Efficiency of Polymeric Coatings for the Conservation of Ancient Egyptian Wall Paintings, El-Qurna Necropolis, Upper Egypt - Marey Mahmoud, Hussein Hassan (Ge-conservacion, 2012)
The present work aims at studying the long-term protection of damaged Egyptian wall paintings (tomb of Ameneminet, No. TT277, Ramesside Period), El-Qurna necropolis, Upper Egypt. To achieve this, the efficiency of some polymeric materials for the consolidation of laboratory samples similar to the ancient murals was evaluated. The climatic conditions of the area play an important role in accelerating the damages process of the paintings. Crystallization cycles of salts exert additional pressure by producing cracking, powdering and flaking, in addition to pulverization of the pictorial layers. Different commercial products based on acrylic and silicone consolidation materials were tested in this study. The evaluation of the consolidation process was performed using the visual observation, scanning electron microscopy (SEM), contact angle values, color measurements and determining the physical and mechanical properties. The results showed that the superior behavior of water repellency was obtained by the micro emulsion Wacker VP 1311. Moreover, the application of the stone strengthener Wacker OH and the acrylic co-polymer Paraloid B82 helped in improving the physical and mechanical properties of the treated samples. In conclusion, Wacker OH could be used to enhance the durability of the inner matrix; however, the application of the microemulsion Wacker VP 1311 as a protective layer will increase the material’s water repellency in areas subjected to moisture or ground water attack.